2016
DOI: 10.1007/s11136-016-1410-7
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal treatment philosophy in Dutch and German NICUs: health-related quality of life in adulthood of VP/VLBW infants

Abstract: A note on versions:The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRAP url' above for details on accessing the published version and note that access may require a subscription.For more information, please contact the WRAP Team at: wrap@warwick.ac.uk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
(41 reference statements)
2
7
0
Order By: Relevance
“…Like Breeman et al 2017 [ 23 ] who reported that lower health-related quality of life was related to cognitive impairment in adulthood, we found cognitive function at five years to be associated with physical health-related quality of life. Further, we found cognitive function at 14 years of age to be associated with the GAF Function subscale.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Like Breeman et al 2017 [ 23 ] who reported that lower health-related quality of life was related to cognitive impairment in adulthood, we found cognitive function at five years to be associated with physical health-related quality of life. Further, we found cognitive function at 14 years of age to be associated with the GAF Function subscale.…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, increasing length of respiratory support and hospital stay in the neonatal period as well as motor problems in adolescence were associated with psychiatric symptoms at 26 years of age [ 21 ]. We also found associations between poor motor function at 23 years of age and mental health problems and lower health-related quality of life at the same age [ 22 ], and others have reported an association between childhood cognitive function and adult health-related quality of life [ 23 ]. A review article highlights decreasing gestational age and lower sociodemographic status as major predictors of adult psychopathology [ 24 ], whereas others have found neither perinatal factors nor childhood cognitive function to predict psychiatric disorders in adulthood [ 25 ].…”
supporting
confidence: 66%
“…As an example, CHIP measured health status and the health status of school-age children born EPT are generally good 8. Furthermore, there is an assumption that, depending on the country, cultural differences impact QoL 34. The lessening QoL in our population is comparable to a recent adult population study where only autonomous adults (without impairment) were respondent 35…”
Section: Discussionmentioning
confidence: 62%
“… 35 36 If EP participants fail to achieve optimum levels of cognitive function once they have reached maturity, then this has implications for health and well-being in later adulthood and old age. 37 …”
Section: Discussionmentioning
confidence: 99%